TOBACCO CESSATION: DO SMOKERS NEED PROFESSIONAL HELP TO QUIT? - Baber Ahad (Gandhara University, 2019)
Tobacco use is considered a risk factor for 6 ofthe 8 leading causesof death worldwide and isknownto cause diseasesaffectingthe heart and lungs1. Tobacco hasa definite rolein the etiologyofa number of dental morbidities, and is an established riskfactor for Oral Cancer and periodontitis. World health organization reported more than a billionsmokersworldwide. Thenumber ofsmokersis increasingand a shift ofincreasednumber of smokersin developing world is noticed. Tobacco isa bigkilleras more than 10% ofadultdeathsannually, fromallcauses are attributedtoit. Moreover,tobacco kills almost five and a half million annuallyand on the average 10 persons per minute2. Considering gravityof thesituation, a global and localtobacco controlstrategybecomes veryimportant. The Government ofPakistan hasincreased taxesontobacco products, bannedits use inpublicplacesto discourageits use. Thisstrategywould helpreducethe number of tobacco productsused byindividuals. But what'smissing isto focus on regular smokers, and assesswhethertheyneed professional help to quit tobacco. Most ofthesmokersfind it difficult to quit on their own, while some successfulquittersconsider motivation, willpower and commitment important factors. Howcan aregularsmoker be motivated isstillnot clear andneedsmore research3.Theself-quitproportion for regular smokersis 3-5%4,which isquite lowand most ofthe tobacco usersfind it difficult to quit, evenafter feelingthe effectsafteryearsofsmoking. The reason could be addictionto dailydose ofnicotineto the brain. Agood number ofsmokerswant to quit at some time, but it is alsonotedthat onlya limitednumber ofthesessmokers have ever tried5. Theclinical practice guidelinesfor treatment ofTobacco use and dependence, recommendstheuse "Five A's"for tobacco cessation6. Thefirst stepofthissmokingcessation protocol is to "ASK" anindividual about current smoking statusand anypreviousattempt to quit smoking. The next step is to "ADVISE",througha clearand strong personalizedmessage andhelp identifyaquitting date. This isfollowed by"ASSESS", whether the smoker isreadyto quit. This isfollowedbythestep "ASSIST", in which literature isprovidedto help thesmoker understand the benefits ofquitting. Thelast stepiscalled "ARRANGE", whichmeans arranging a follow upvisit,usuallyafter 1 to2 weeksofquitting date. Health professionalsare consideredas acredible source ofinformation.Familyphysicians canplaya veryimportant part in helping their patients who are regular smokers. Bybringing "Five A's" modelinto practice,a physiciancangivea better opportunityto asmoker to understand the health hazardsoftobacco use, andknowthe benefits ofquittingperiodically. Thiscan lead to a higherpercentageof successfultobacco quitters. Otherhealthcare professionals, who can playanimportant role in helpingsmokersquit, are the dentalprofessionals. Apatient would spend more time in a dental office and routine dentaladvice should alsoinclude quit tobacco, alongwith oralhygieneinstructions and dietaryadvice. Dentalassociations should encourage their membersto advisepatients about oral and systemic hazards of tobaccoproducts.